Uporabe ljudskih pravljic v legitimizaciji političnih ideologij 20. stoletja - Horvat, Marjan (Acta Histriae, 2022)
In the paper, I investigate the use of folktales in the historical legitimization of a particular type of socio-political transformation: Yugoslav self-governing socialism. In this respect I address a less researched and complex topic, while the Yugoslav ideology of self-governance, compared to other 20th century political ideologies, was based on discontinuity – a break with tradition and the past. In order to sharpen the specific function of the narrative tradition in Yugoslav socialism and on the basis of the sociological theory of fairy tales and Walter Benjamin’s insights into the role of the narrative tradition, which he reflected on as a transhistorical medium for the transmission of collective experiences – I have devised a research approach that differentiates the epistemic and ideological function of fairy tales. I test this approach via the example of the appropriation of folktales in the Third Reich and Soviet communist regime, and then turn to an analysis of these mechanisms in the context of Yugoslav self-government. On the basis of various theories and understanding of Yugoslav selfgovernance (E. Kardelj, J. Županov, P. Matvejević, D. Suvin, B. Jakovljević etc.), I put forward that the tradition in the latter was expressed in the prism of an alienation effects. I illustrate this with an extensive comparative and transhistorical analysis of the fairy-tale motif of The Gigantic Turnip, especially its unusual Slovenian version which can be perceived as a critical commentary of the socialist motto “together we are stronger”. In the conclusion, I reflect upon the theoretical consequences of the Yugoslav self-governing project from the point of view of the theory of societal transformation, and connect this topic to the dilemmas concerning contemporary risks such as the climate crisis, which have no historical equivalent.
Keywords: autogestione jugoslava; cambiamenti sociali; družbene spremembe; folk tales; ideologie politiche; jugoslovansko samoupravljanje; ljudske pravljice; political ideologies; politične ideologije; racconti popolari; revolucija; revolution; rivoluzione; societal transformation; Walter Benjamin; Yugoslav self-management